Unsal Oskay's anthology on Walter Benjamin - AVCI, ARTUN (MARMARA UNIV, FAC COMMUNICATION, 2015)
This study involves the texts Unsal Oskay has written on Benjamin's works. The aim of the study is to enable these texts starting by contextualizing the methodological dimensions as Oskay stresses out, understanding Benjamin is concieving his methodology. In the first part, the contribution is on Oskay's texts related to Benjamin's life as well as his epistemology and methodology. In the second part the discussion will be on Benjamin's concept of history and how Unsal Oskay metaphrases these theories. And in the final part Oskay's works on Benjamin's life long Arcades Project (Das Passagen-Werk) will be discussed. The final part formulated Oskay's interpretation as fragmented texts inspired by the Arcades Project. The study ends by targeting the present Oskay's work and on Benjamin and how Benjamin contributed to the field of cultural and communication studies.
Keywords: Unsal Oskay; Walter Benjamin; Flaneur; Arcades Project; Modernism